ISOLATION AND IDENTIFICATION OF BACTERIA REMOVING NITRITE, NITRATE, AND AMMONIUM FROM BIOBALLS FILTER - Qoriatul Ilma; Achmad Dinoto; Ninu Setianingrum; Mulyadi Mulyadi; Dwi Agustyani; Nani Radiastuti; Heddy Julistiono (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
The presence of effective bacteria removing nitrite, nitrate, and ammonia in a recirculating aquaculture system (RAS) is necessary to attenuate their toxicity to fish. The research was conducted to find bacteria that can be cultured and reduce nitrite, nitrate, and ammonium. Sixteen bacterial colonies were isolated from bioballs of RAS biofilter and tested for their ability to reduce nitrite or nitrate concentrations. Using a simple indicator paper for nitrite and nitrate, four isolates that reduced nitrite and nitrate concentrations, namely K1NA3, K2NA3, CNA1, and PRO4NA1 were selected. The four isolates were then evaluated for the metabolism of nitrate, nitrite, and ammonium compounds using the spectrophotometry method. Results showed that the isolates K1NA3, CNA1, and PRO4NA1 reduced nitrite concentration but produced ammonium, whereas K1NA3 isolate was able to reduce nitrate concentration but produced both nitrite and ammonium. Experiments in reducing ammonium levels in the synthetic waste media showed the ability of four isolates to reduce ammonium levels after six days despite producing nitrite. Based on the 16S rRNA gene analysis, these isolates have a close relationship to Pseudomonas otitidis (KINA3 and K2NA3), Acinetobacter cumulans (CNA1), and Vogesella perlucida (PRO 4NA1).